Identifying Individual T Cell Receptors of Optimal Avidity for Tumor Antigens - Hebeisen, Michael; Allard, Mathilde; Gannon, Philippe O.; Schmidt, Julien; Speiser, Daniel E.; Rufer, Nathalie (Frontiers in Immunology, 2015)
Cytotoxic T cells recognize, via their T cell receptors (TCRs), small antigenic peptides presented by the Major Histocompatibility Complex (pMHC) on the surface of professional antigen presenting cells (APC), and infected or malignant cells. The efficiency of T cell triggering critically depends on TCR binding to cognate pMHC, i.e. the TCR-pMHC structural avidity. The binding and kinetic attributes of this interaction are key parameters for protective T cell-mediated immunity, with stronger TCR-pMHC interactions conferring superior T cell activation and responsiveness than weaker ones. However, high avidity TCRs are not always available, particularly among self/tumor antigen-specific T cells, most of which are eliminated by central and peripheral deletion mechanisms. Consequently, systematic assessment of T cell avidity can greatly help distinguishing protective from non-protective T cells. Here, we review novel strategies to assess TCR-pMHC interaction kinetics, enabling the identification of the functionally most-relevant T cells. We also discuss the significance of these technologies in determining which cells within a naturally occurring polyclonal tumor-specific T cell response would offer the best clinical benefit for use in adoptive therapies, with or without T cell engineering.